2019
DOI: 10.1001/jamanetworkopen.2019.0896
|View full text |Cite
|
Sign up to set email alerts
|

Association of Chemerin Plasma Concentration With Risk of Colorectal Cancer

Abstract: Key Points Question Is there an association between peripheral concentrations of the proinflammatory biomarker chemerin and incident colorectal cancer? Findings In this case-cohort study that included 221 incident colorectal cancer cases and 2329 cancer-free participants, higher circulating plasma chemerin concentration was associated with a greater risk of colorectal cancer. This association was independent of known risk factors for colorectal cancer, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 58 publications
3
21
0
Order By: Relevance
“…Recent studies described a role of chemerin in CRC pathophysiology and diagnosis [7,8,9]. Chemerin is a chemoattractant protein most abundant in adipocytes and hepatocytes [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies described a role of chemerin in CRC pathophysiology and diagnosis [7,8,9]. Chemerin is a chemoattractant protein most abundant in adipocytes and hepatocytes [10].…”
Section: Introductionmentioning
confidence: 99%
“…High plasma chemerin predicted a greater risk of CRC. Notably, this association was still significant when CRC risk factors such as age, body mass index and dietary habits were considered [8]. A second study detected higher chemerin in patients with CRC compared to healthy controls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, chemerin is thought to exert chemotactic, adipogenic, and angiogenic functions. Higher chemerin levels are associated with CRC risks [278,279] A schematic summarizing colon disease-associated adipokine alterations and the basis is provided in Figure 2.…”
Section: Other Adipokinesmentioning
confidence: 99%
“…The National Comprehensive Cancer Network Guideline recommends chemotherapy combined with CET or BV as a first-line treatment for metastatic colorectal cancer (Eichelmann et al, 2019). Since the approval of targeted drugs in the early 21st century, a number of large clinical studies have shown that the overall survival (OS) of patients with metastatic colorectal cancer has increased by nearly one year compared with chemotherapy alone (Modest et al, 2015;Venook et al, 2017).…”
Section: Introductionmentioning
confidence: 99%